Ritualistik - en ny religionshistorisk disciplin - Podemann Sørensen, Jørgen (Religionsvidenskabeligt tidsskrift, 1992)
The idea of ritualistics as a new discipline in history of religions is based on practical as well as theoretical considerations. The broad, comparative discipline sometimes called the phenomenology of religion has above all adressed a number of interesting themes, usually without distinguishing levels of analysis. In discussions of themes like the idea of god or divine kingship, the failure to recognize ritual as a distinct level not immediately compatible with levels of beliefs, ideas, attitudes etc. has entailed inconsistencies and subsequent diacronical fragmentation of contemporary source material. By introducing the new discipline of ritualistics to replace part of the phenomenology of religion, it may be hoped that some of the pitfalls of an uncritical thematic approach may be avoided. Ritualistics is not in itself a new method, but a discipline that defines a level of analysis as do linguistic disciplines like phonetics, morphology, syntax, semantics; it may thus be considered a first step towards an analogous theoretical contruction of the object of history of religions.